Comparison of the molecular properties and volatile compounds of Maillard reaction products derived from animal- and cereal-based protein hydrolysates. (30th July 2022) - Chiang, Jie Hong; Yeo, Michelle Ting Yun; Ong, Dayna Shu Min; Henry, Christiani Jeyakumar
Highlights: Chicken bone, wheat, and rice proteins were substrates for flavour development. Enzyme-substrate ratios for these proteins were obtained via Michaelis-Menten model. Lowered free amino acids after heating indicated the occurrence of Maillard reaction. Pyrazines, furan, and thioethers were detected in the Maillard reaction products. Abstract: The changes in the molecular properties and volatile compounds of Maillard reaction products obtained from chicken bone extract (CBE), wheat protein (WP), and rice protein (RP) hydrolysates were compared in this study. Pressure cooking was used to prepare CBE, which was then filtered, defatted, and concentrated. The optimum enzyme-substrate (E/S) ratio of CBE, WP, and RP on Flavourzyme® using the Michaelis-Menten model was 4.0, 5.7, 4.8% w/w, respectively. The occurrence of the Maillard reaction was demonstrated by the lowering of pH, low molecular weight peptides (<1K Da), and total free amino acids after the samples were heat-treated. Volatile compounds were analysed using gas chromatography-mass spectrometry (GC–MS) in conjunction with headspace solid-phase microextraction (SPME) sampling. Pyrazines, furan, and thioethers were detected in the MRPs of CBE, WP and RP. It was concluded that the MRPs of CBE, WP, and RP could be used as potential natural flavours in food applications.